Grenada. Significant achievements 2010-2017 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The main activities carried out by the Institute in Granada are identified, during the period from 2010 to 2017, with respect to the needs and interests of the country, strengthening issues such as sustainability, organic agriculture, soil health, public policies, technologies new, good agricultural practices, resilience against climate change and pest control. Likewise, work was done on pest management, on the use of organic pesticides, organic fertilizers, such as manure, and on food safety and sanitation. Finally, it was supported in financial negotiations and in the inclusion of women in agriculture.